A Journey through Manufacturing and Supply Chain Strategy Research A Tribute to Professor Gianluca Spina - Bartezzaghi, Emilio; Cagliano, Raffaella; Caniato, Federico; Ronchi, Stefano (Springer International Publishing : Imprint: Springer, 2016)
The book is a 'Liber Amicorum' for the late Gianluca Spina, Professor at Politecnico di Milano, Italy, who was well-known and respected in the European Operations Management research community. It consists of reprints of 7 of his most important cited and representative papers, spanning his research career from the early 90s and presenting his research trajectory. Each paper has original comments by one or two relevant international scholars in the field, who were also his close friends. These offer a critical discussion of the papers' content, as well as a discussion of their contribution to the academic debate since publication.